2019
DOI: 10.2174/1389202920666190603123040
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Low Dose Bisphenol-A (BPA) Exposure in Human Prostate Cells

Abstract: : Endocrine disrupting compounds (EDCs) have the potential to cause adverse effects on wildlife and human health. Two important EDCs are the synthetic estrogen 17α-ethynylestradiol (EE2) and bisphenol-A (BPA) both of which are xenoestrogens (XEs) as they bind the estrogen receptor and disrupt estrogen physiology in mammals and other vertebrates. In the recent years the influence of XEs on oncogenes, specifically in relation to breast and prostate cancer has been the subject of considerable study. Methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 105 publications
1
6
0
Order By: Relevance
“…A whole-genome microarray performed in healthy primary human prostate epithelial cells has shown that BPA treatment affects the expression of genes relevant for cancer development and progression in prostate cells, involved in pathways modulating angiogenesis, cell proliferation, cell cycle, DNA replication and repair, metabolism, inflammation, and immune response pathways. In parallel, BPA deregulates the expression of transcripts relevant to epigenetic changes, such as histone and DNA methylation modifying enzymes [167]. Similar results have been obtained by Fatma Karaman et al who performed PCR arrays in the human prostate adenocarcinoma PC-3 cell line to investigate the transcriptional profiling of chromatin-modifying enzymes and DNA methylation levels of tumor suppressor genes including p16, Cyclin D2, and Rassf1.…”
Section: Bpa-induced Epigenetic Modifications In Cancersupporting
confidence: 73%
“…A whole-genome microarray performed in healthy primary human prostate epithelial cells has shown that BPA treatment affects the expression of genes relevant for cancer development and progression in prostate cells, involved in pathways modulating angiogenesis, cell proliferation, cell cycle, DNA replication and repair, metabolism, inflammation, and immune response pathways. In parallel, BPA deregulates the expression of transcripts relevant to epigenetic changes, such as histone and DNA methylation modifying enzymes [167]. Similar results have been obtained by Fatma Karaman et al who performed PCR arrays in the human prostate adenocarcinoma PC-3 cell line to investigate the transcriptional profiling of chromatin-modifying enzymes and DNA methylation levels of tumor suppressor genes including p16, Cyclin D2, and Rassf1.…”
Section: Bpa-induced Epigenetic Modifications In Cancersupporting
confidence: 73%
“…Prostate is an effector organ of hormones, and hormone receptors are indispensable for its normal development and metabolism. Low-level BPA, comparable to those routinely detected in the environment, critically affects global transcriptomic responses in prostate epithelial cells through cross-regulation of the signaling networks (Renaud et al, 2019). Potential effects for prostate gland are further compounded by the BPA-associated changes of androgen-signaling pathway and estrogen-signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…BPA exposure of newborn rats resulted in the modulation of the methylation of promoter regions of genes related to embryonic SC pluripotency, cell-tocell signaling and interaction, cell-mediated immune response, cellular growth and proliferation, nucleic acid metabolism, molecular transport, cellular assembly, and organization (Cheong et al, 2016). The epigenetic changes induced by BPA exposure have been corroborated not only in animal models but in vitro experiments, where this EDC also modified the epigenetic signature of transcripts encoding nuclear hormone receptors as well as histone and DNA methylation in prostate epithelial cells (Renaud et al, 2019). In addition, this compound can also induce centrosomal abnormalities, microtubule nucleation, and anchorageindependent growth in prostate cancer cell lines (Tarapore et al, 2014).…”
Section: Prostate Cancer and Perinatal Or Neonatal Exposure Of Bispmentioning
confidence: 90%